Antimicrobial Susceptibility Patterns of Escherichia coli from Urine Isolates - Shailabi, Taher I. Mahmod; Aldeeb, Osama H.; Almaedani, Abdullah F.; Borwis, Elham O.; Amer, Samar A. (Al-Mukhtar Journal of Sciences, 2022)
Urinary tract infections (UTIs) are predominantly caused by Escherichia coli (E. coli). Increasing E. coli resistance to antibiotics is a major concern worldwide. Since UTIs are often treated by trial and error, measuring antimicrobial resistance (AMR) is important. However, there isn't much information about the rate of antimicrobial resistance to E. coli in the Libyan community. To determine rate of antimicrobial susceptibility patterns of E. coli urine isolates, in Al-Bayda, Libya. A retrospective study, in which 104 E. coli urine isolates were conducted using the antimicrobial susceptibility profile (antibiogram) of six different antibiotics against E. coli, isolates, were collected from several medical laboratories. Out of the 104 E. coli urine isolates, the MDR was 39.4%. The overall frequency of isolates resistant to ceftriaxone was 62.5%, trimethoprim-sulfamethoxazole (TMP-SMZ)(54.8%), Amoxicillin-Clavulanic acid (47.11%), ciprofloxacin (26%), nitrofurantoin (18.26%), and levofloxacin (15.4%). Prevalence of AMR among Libyan outpatient urine-isolated E. coli was high, with a high incidence of multidrug-resistance. The knowledge of antibiotic resistance rates in the region helps inform empiric treatment of community-onset UTI and highlights the antibiotic resistance profile to clinicians.